ROLE COLOUR PLAYS IN INFLUENCING CONSUMER BEHAVIOUR - Rathee, Rupa; Rajain, Pallavi (Universitas Prasetiya Mulya, 2019)
The ability of colours to attract attention has been used for a long time by marketers to gain customer?s attention. It has been found in several studies that if there is a mismatch in representation of colour associations the colour becomes an eyesore. Therefore, the present study was conducted to understand the role colour plays in influencing consumer behaviour. For this an online survey form was circulated among respondents to study their colour preferences. It was found that yellow colour was preferred the least and blue the most. There were significant differences in choices made by the two genders. The results indicated that colour influenced customer?s decision and brand recall while making purchases. It was also found that there was significant difference among respondents regarding purchase of warm and cool colours as well as warm and neutral colours.